Sodium-ion battery positive electrode material, preparation method thereof, electrode plate and battery
Patent Information
- Application Number
- CN202511410923.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-29
AI Technical Summary
[0006]本申请的目的在于提供一种钠离子电池正极材料及其制备方法、极片和电池,以解决钠电层氧正极材料的低温放电容量保持率差、循环容量衰减快的问题
[0017]与现有技术相比,本申请的有益效果包括:
Smart Images

Figure CN121260769B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of sodium-ion batteries, and more particularly to a sodium-ion battery cathode material, its preparation method, electrode sheet, and battery. Background Technology
[0002] With the rapid development of sodium-ion batteries, O3-structured sodium-ion layered oxide cathode materials have attracted widespread attention due to their wide availability of raw materials, low cost, high specific capacity, and good cycle stability. However, O3-type layered oxide cathode materials exhibit low low-temperature discharge capacity retention. Furthermore, the specific capacity utilization and electrode compaction density of sodium-ion layered oxide cathode materials are both at relatively low levels.
[0003] To improve the energy density of sodium ion layer oxygen cathode materials, existing technologies typically employ reducing particle size to increase sodium ion insertion / extraction sites and shorten sodium ion diffusion paths, thereby achieving higher discharge capacity and rate performance.
[0004] However, reducing the particle size increases the contact area with the electrolyte, exacerbating side reactions between the cathode material particle surface and the electrolyte. This causes the layered structure on the particle surface to transform into a rock-salt-like phase, hindering the re-intercalation of sodium ions and resulting in poorer cycle performance. Furthermore, smaller particle sizes can also lead to severe transition metal dissolution during cycling, especially when high-valence Ni... 4+ Fe 4+ When the sodium ion melts and migrates from the positive electrode to the negative electrode surface, it catalyzes the decomposition of the solid electrolyte membrane (SEI). The continuous decomposition and repair of the SEI membrane consumes a large amount of active sodium, resulting in irreversible capacity loss and reducing the energy density and safety performance of the battery. In addition, trace amounts of HF are usually generated during the cycling process of sodium-ion batteries. HF molecules are very easy to adsorb on the close-packed crystal plane (003) of transition metals with high symmetry and low surface energy, which leads to the dissolution of more transition metals.
[0005] Therefore, there is an urgent need to provide a sodium-ion battery cathode material to solve the above problems. Summary of the Invention
[0006] The purpose of this application is to provide a sodium-ion battery cathode material and its preparation method, electrode sheet and battery, so as to solve the problems of poor low-temperature discharge capacity retention and rapid cycle capacity decay of sodium-ion battery cathode materials.
[0007] To achieve the above objectives, the first aspect of this application provides a sodium-ion battery cathode material, including a substrate and a coating layer disposed on the surface of the substrate; The general structural formula of the matrix is: Na a Ni x Fe y Mn zO2, where 1.05≥a≥0.80, 0.5≥x≥0.1, 0.4≥y≥0.1, 0.8≥z≥0.1; The coating layer comprises an oxide containing M' and sodium; M' includes one or more of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo; Its XRD pattern satisfies the following: the ratio of the diffraction peak intensities of the 003 crystal plane to those of the 104 crystal plane is N, where 1.35≤N≤3.5; The ratio of the average length to the average height of the sodium-ion battery cathode material is M, where 1.02 ≤ M ≤ 10.91.
[0008] Optionally, the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) 1.4≤N≤2.35, 1.5≤M≤6.1; (2) The 2θ range of the 003 peak of the sodium-ion battery cathode material is 16.2-16.9, and the 2θ range of the 104 peak is 41.4-41.8; (3) The length of the sodium-ion battery cathode material is 2.0-8.73 μm and the height is 0.8-1.96 μm.
[0009] Optionally, the matrix is further doped with element M, and the general structural formula of the doped matrix is: Na a Ni x Fe y Mn z M 1-x-y-z O2, wherein 1.05≥a≥0.80, 0.5≥x≥0.1, 0.4≥y≥0.1, 0.8≥z≥0.1, 1.0>1-xzy>0; M includes one or more of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
[0010] Optionally, the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) The D50 of the sodium-ion battery cathode material is 1.0-12 μm; (2) The specific surface area of the sodium-ion battery cathode material is 0.2-1.5 m². 2 / g.
[0011] A second aspect of this application provides a method for preparing the sodium-ion battery cathode material described above, comprising: The nickel salt, iron salt, and manganese salt are first mixed to obtain a mixed metal salt solution; Under a nitrogen atmosphere, a mixed metal salt solution, sodium hydroxide solution and ammonia solution are introduced into a first base solution containing sodium hydroxide and ammonia water to carry out a first coprecipitation reaction to obtain a seed slurry while maintaining a constant pH value. A mixed metal salt solution, sodium hydroxide solution, and ammonia solution are introduced into a second bottom solution containing the seed slurry, sodium hydroxide, and ammonia water to carry out a second coprecipitation reaction to obtain a hydroxide precursor; The hydroxide precursor and sodium source are mixed to obtain a mixture. The mixture is then pre-sintered and first calcined under an oxygen-containing atmosphere to obtain a first calcined material. The first calcined material and the M'-containing compound are mixed in a third time and then calcined in a second time to obtain a sodium-ion battery cathode material. During the first coprecipitation reaction, the pH value is constant; during the second coprecipitation reaction, the pH value gradually decreases.
[0012] Optionally, the method for preparing the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) The nickel salt includes nickel sulfate; (2) The iron salts include ferric sulfate; (3) The manganese salt includes manganese sulfate; (4) The M'-containing compound includes one or more of the oxides, chlorides, fluorides, hydroxides, carbonates, nitrates and acetates of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La and Mo; (5) The sodium source includes one or more of sodium carbonate, sodium hydroxide, and sodium acetate; (6) When performing the first mixing and / or the second mixing, a compound containing M is also added, said compound containing M including one or more oxides, chlorides, fluorides, hydroxides, carbonates, nitrates and acetates of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
[0013] Optionally, the method for preparing the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) During the first mixing, the molar ratio of nickel in the nickel salt, iron in the iron salt, and manganese in the manganese salt is 0.1-0.5: 0.1-0.4: 0.1-0.8; (2) The molar ratio of the hydroxide precursor to sodium in the sodium source is 1:0.85-1.15; (3) The mass of M' in the M'-containing compound accounts for 500-8000 ppm of the mass of the mixture obtained by the third mixing; (4) The mass of M in the M-containing compound accounts for 500-10000 ppm of the mass of the mixture obtained by the second mixing.
[0014] Optionally, the method for preparing the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) The pH value of the first base solution and the first coprecipitation reaction is 11.2-11.9; (2) The time for the first coprecipitation reaction is 40-48 hours; (3) The alkalinity of the first coprecipitation reaction and the second coprecipitation reaction are each 3-9 g / L, and the temperature is each 55-65℃. (4) The pH value of the second substrate is 10.5-11.0; (5) The endpoint pH value of the second coprecipitation is 10-10.4; (6) The second coprecipitation time is 36-48 hours; (7) The purity of nitrogen in the nitrogen atmosphere is greater than or equal to 99.5%; (8) Before the second mixing, the hydroxide precursor is dried at a temperature of 100-300°C for 2-6 hours. (9) The heating rate of the pre-sintering is 1-15℃ / min, the final temperature is 400-550℃, and the time is 4-12h; (10) The heating rate of the first calcination is 1-15℃ / min, the final temperature is 800-1100℃, and the time is 10-24h; (11) The heating rate of the second calcination is 1-15℃ / min, the final temperature is 450-800℃, and the time is 4-12h.
[0015] A third aspect of this application provides a positive electrode sheet, comprising the aforementioned sodium-ion battery positive electrode material or a sodium-ion battery positive electrode material prepared by the aforementioned method.
[0016] A fourth aspect of this application provides a battery including the aforementioned positive electrode.
[0017] Compared with the prior art, the beneficial effects of this application include: The sodium-ion battery cathode material provided in this application fundamentally improves the high-rate performance and low-temperature cycle capacity retention of the battery by controlling the morphology characteristics and element coating design of the sodium-ion cathode material particles; it also alleviates the internal stress generated in the cathode material during charging and discharging and stabilizes the integrity of the crystal structure.
[0018] The method for preparing sodium-ion battery cathode material provided in this application is simple, efficient, and can be mass-produced industrially. It can precisely control the width and thickness of the layered cathode material of sodium-ion battery, increase the electrochemical reaction area, and significantly improve the rate performance and low-temperature charge-discharge performance of sodium-ion battery.
[0019] The electrode and battery provided in this application have high low-temperature discharge capacity retention and slow cycle capacity decay. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0021] Figure 1 SEM image of the hydroxide precursor provided in Example 1; Figure 2 The XRD pattern of the sodium-ion battery cathode material provided in Example 1; Figure 3 SEM image of the sodium-ion battery cathode material provided in Example 1; Figure 4 SEM image of the hydroxide precursor provided for Comparative Example 1; Figure 5 XRD pattern of the sodium-ion battery cathode material provided for Comparative Example 1; Figure 6 SEM image of the sodium-ion battery cathode material provided for Comparative Example 1; Figure 7 XRD pattern of the sodium-ion battery cathode material provided for Comparative Example 2; Figure 8 SEM image of the sodium-ion battery cathode material provided for Comparative Example 2. Detailed Implementation
[0022] First, the solution provided in this application will be explained in more detail as follows: The first aspect of this application provides a sodium-ion battery cathode material, including a substrate and a coating layer disposed on the surface of the substrate; The general structural formula of the matrix is: Na a Ni x Fe y Mnz O2, where 1.05≥a≥0.80, 0.5≥x≥0.1, 0.4≥y≥0.1, 0.8≥z≥0.1; Optionally, in the general structural formula of the matrix, a can be any value between 0.8, 0.9, 1, 1.05 or 0.8-1.05, x can be any value between 0.1, 0.2, 0.3, 0.4, 0.5 or 0.1-0.5, y can be any value between 0.1, 0.2, 0.3, 0.4 or 0.1-0.4, and z can be any value between 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.1-0.8; The coating layer comprises an oxide containing M' and sodium; M' includes one or more of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
[0023] Its XRD pattern satisfies the following: the ratio of the diffraction peak intensities of the 003 crystal plane to those of the 104 crystal plane is N, where 1.35≤N≤3.5; Optionally, N can be 1.35, 2, 3, 3.5, or any value between 1.35 and 3.5; It should be noted that the ratio of the diffraction peak intensities of the (003) crystal plane to those of the (104) crystal plane specifically refers to the ratio of the peak intensity (i.e., peak height) of the diffraction peak corresponding to the (003) crystal plane to the peak intensity (i.e., peak height) of the diffraction peak corresponding to the (104) crystal plane. The ratio of the average length to the average height of the sodium-ion battery cathode material is M, where 1.02 ≤ M ≤ 10.91.
[0024] Optionally, M can be any value between 1.02, 2, 3, 4, 5, 6, 7, 8, 9, 10, 10.91 or 1.02-10.91.
[0025] It should be noted that the average length and average height of the sodium-ion battery cathode material are represented by the inactive crystal facet (003) and the active crystal facet (010) of the sodium-ion cathode material particle, respectively. The 003 crystal facet serves as the close-packed facet of the transition metal, which restricts the interlayer migration of sodium ions in the transition metal layer, while the 104 crystal facet serves as the active facet for sodium ion insertion and extraction. Increasing the exposure ratio of this tilted crystal facet can give the material excellent rate performance and cycle stability.
[0026] It should also be noted that when more active crystal faces are exposed, more and more direct Na can be provided. +Migration channels lower the diffusion barrier, but highly active crystal faces typically have high surface energy and are also the main regions where phase transitions occur. This can easily lead to crystal facet slip and microcrack formation, causing side reactions with the electrolyte, accelerating interfacial degradation, and resulting in decreased cycle performance. Therefore, while meeting high-rate performance requirements, it is necessary to control a certain proportion of inactive crystal faces to ensure that the material also possesses cycle stability.
[0027] In some embodiments, the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) 1.4≤N≤2.35, 1.5≤M≤6.1; Optionally, N can be any value between 1.4, 1.5, 1.8, 2, 2.2, 2.35, or 1.4-2.35, and M can be any value between 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.1, or 1.5-6.1. It should be noted that by controlling N and M within this range, the cathode material has better rate performance, fewer microcracks on the active crystal face, and higher cycle stability. (2) The 2θ range of the 003 peak of the sodium-ion battery cathode material is 16.2-16.9, and the 2θ range of the 104 peak is 41.4-41.8; Optionally, the 2θ range of the 003 peak of the sodium-ion battery cathode material can be any value between 16.2, 16.4, 16.6, 16.8, 16.9 or 16.2-16.9, and the 2θ range of the 104 peak can be any value between 41.4, 41.5, 41.6, 41.7, 41.8 or 41.4-41.8. (3) The length of the sodium-ion battery cathode material is 2.0-8.73 μm and the height is 0.8-1.96 μm.
[0028] Optionally, the length of the sodium-ion battery cathode material can be any value between 2μm, 4μm, 6μm, 8μm, 8.73μm, or 2-8.73μm, and the height can be any value between 0.8μm, 1μm, 1.5μm, 1.96μm, or 0.8-1.96μm.
[0029] In some embodiments, the matrix is further doped with element M, and the general structural formula of the doped matrix is: Na a Ni x Fe y Mn z M 1-x-y-zO2, wherein 1.05≥a≥0.80, 0.5≥x≥0.1, 0.4≥y≥0.1, 0.8≥z≥0.1, 1.0>1-xzy>0; M includes one or more of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
[0030] Optionally, 1-xzy can be any value between 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or greater than 0 and less than 1.
[0031] It is important to note that introducing M dopant can effectively adjust the relative positions of the d-band centers of the transition metal and the p-band centers of oxygen, enhancing metal-oxygen (MO) covalentity, improving the stability of lattice oxygen under high SOc, and making it less prone to O2 molecule precipitation. Furthermore, during sodium ion insertion / extraction, the layered structure of the material undergoes slippage accompanied by significant volume changes. The M dopant acts as a "pillar" or "buffer," enhancing the crystal structure's resilience to the stress generated by sodium ion insertion / extraction.
[0032] In some embodiments, the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) The D50 of the sodium-ion battery cathode material is 1.0-12 μm; Optionally, the D50 of the sodium-ion battery cathode material can be any value between 1μm, 2μm, 4μm, 6μm, 8μm, 10μm, 12μm or 1-12μm; (2) The specific surface area of the sodium-ion battery cathode material is 0.2-1.5 m². 2 / g.
[0033] Optionally, the specific surface area of the sodium-ion battery cathode material can be 0.2 m². 2 / g, 0.5 m 2 / g、1 m 2 / g, 1.5m 2 / g or 0.2-1.5 m 2 Any value between / g.
[0034] A second aspect of this application provides a method for preparing the sodium-ion battery cathode material described above, comprising: The nickel salt, iron salt, and manganese salt are first mixed to obtain a mixed metal salt solution; Under a nitrogen atmosphere, a mixed metal salt solution, sodium hydroxide solution and ammonia solution are introduced into a first base solution containing sodium hydroxide and ammonia water to carry out a first coprecipitation reaction to obtain a seed slurry while maintaining a constant pH value. A mixed metal salt solution, sodium hydroxide solution, and ammonia solution are introduced into a second bottom solution containing the seed slurry, sodium hydroxide, and ammonia water to carry out a second coprecipitation reaction to obtain a hydroxide precursor; The hydroxide precursor and sodium source are mixed to obtain a mixture. The mixture is then pre-sintered and first calcined under an oxygen-containing atmosphere to obtain a first calcined material. The first calcined material and the M'-containing compound are mixed in a third time and then calcined in a second time to obtain a sodium-ion battery cathode material. During the first coprecipitation reaction, the pH value is constant; during the second coprecipitation reaction, the pH value gradually decreases.
[0035] In some embodiments, the method for preparing the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) The nickel salt includes nickel sulfate; (2) The iron salts include ferric sulfate; (3) The manganese salt includes manganese sulfate; (4) The M'-containing compound includes one or more of the oxides, chlorides, fluorides, hydroxides, carbonates, nitrates and acetates of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La and Mo; (5) The sodium source includes one or more of sodium carbonate, sodium hydroxide, and sodium acetate; (6) When performing the first mixing and / or the second mixing, a compound containing M is also added, said compound containing M including one or more oxides, chlorides, fluorides, hydroxides, carbonates, nitrates and acetates of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
[0036] In some embodiments, the method for preparing the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) During the first mixing, the molar ratio of nickel in the nickel salt, iron in the iron salt, and manganese in the manganese salt is 0.1-0.5: 0.1-0.4: 0.1-0.8; Optionally, during the first mixing, the molar ratio of nickel in the nickel salt, iron in the iron salt, and manganese in the manganese salt can be any value between 0.1:0.1:0.1, 0.25:0.1:0.1, 0.5:0.1:0.1, 0.2:0.1:0.1, 0.1:0.4:0.1, 0.1:0.1:0.4, 0.1:0.1:0.8, or 0.1-0.5:0.1-0.4:0.1-0.8. (2) The molar ratio of the hydroxide precursor to sodium in the sodium source is 1:0.85-1.15; Optionally, the molar ratio of sodium in the hydroxide precursor and the sodium source can be any value between 1:0.85, 1:0.9, 1:1, 1:1.15, or 1:0.85-1.15; (3) The mass of M' in the M'-containing compound accounts for 500-8000 ppm of the mass of the mixture obtained by the third mixing; Optionally, the mass of M' in the M'-containing compound is any value between 500 ppm, 1000 ppm, 2000 ppm, 4000 ppm, 6000 ppm, 8000 ppm, or 500-8000 ppm of the mass of the mixture obtained by the third mixing. (4) The mass of M in the M-containing compound accounts for 500-10000 ppm of the mass of the mixture obtained by the second mixing.
[0037] Optionally, the mass percentage of M in the M-containing compound is any value between 500 ppm, 1000 ppm, 2000 ppm, 4000 ppm, 6000 ppm, 8000 ppm, 10000 ppm, or 500-10000 ppm of the mass of the mixture obtained from the second mixing. In some embodiments, the method for preparing the sodium-ion battery cathode material satisfies at least one of the following conditions: (1) The pH value of the first base solution and the first coprecipitation reaction is 11.2-11.9; Optionally, the pH value of the first base solution and the first coprecipitation reaction can be 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9 or any value between 11.2 and 11.9; (2) The time for the first coprecipitation reaction is 40-48 hours; Optionally, the time for the first coprecipitation reaction can be any value between 40 h, 44 h, 48 h, or 40-48 h; (3) The alkalinity of the first coprecipitation reaction and the second coprecipitation reaction are each 3-9 g / L, and the temperature is each 55-65℃. Optionally, the alkalinity of the first coprecipitation reaction and the second coprecipitation reaction can be independently 3 g / L, 6 g / L, 9 g / L or any value between 3 and 9 g / L, and the temperature can be independently 55℃, 60℃, 65℃ or any value between 55 and 65℃. (4) The pH value of the second substrate is 10.5-11.0; Optionally, the pH value of the second substrate can be any value between 10.5, 10.6, 10.7, 10.8, 10.9, 11, or 10.5-11; (5) The endpoint pH value of the second coprecipitation is 10-10.4; Optionally, the endpoint pH value of the second coprecipitation can be any value between 10, 10.1, 10.2, 10.3, 10.4 or 10-10.4; It should be noted that when the pH value is within this range and gradually decreases as the reaction proceeds, it is conducive to the continuous growth of crystal nuclei in the reactor, thereby achieving uniform growth in the thickness direction. When the pH value is lower than the above range, the metal elements may not be completely precipitated, resulting in the precursor components deviating from the designed formula and inaccurate stoichiometry. (6) The second coprecipitation time is 36-48 hours; Optionally, the second co-precipitation time can be any value between 36h, 40h, 44h, 48h, or 36-48h; (7) The purity of nitrogen in the nitrogen atmosphere is greater than or equal to 99.5%; Optionally, the purity of nitrogen in the nitrogen atmosphere can be 99.5%, 99.9%, 99.99%, or any value greater than or equal to 99.5%. (8) Before the second mixing, the hydroxide precursor is dried at a temperature of 100-300°C for 2-6 hours. Optionally, the drying temperature can be any value between 100℃, 200℃, 300℃ or 100-300℃, and the time can be any value between 2h, 4h, 6h or 2-6h; (9) The heating rate of the pre-sintering is 1-15℃ / min, the final temperature is 400-550℃, and the time is 4-12h; Optionally, the heating rate of the pre-sintering can be any value between 1℃ / min, 5℃ / min, 10℃ / min, 15℃ / min or 1-15℃ / min, the final temperature can be any value between 400℃, 450℃, 500℃, 550℃ or 400-550℃, and the time can be any value between 4h, 8h, 12h or 4-12h. It should be noted that pre-calcination can remove the water of crystallization in the hydroxide precursor and the decomposition of sodium salt to generate Na2O, thereby improving the sufficiency of the solid-phase reaction in the subsequent high-temperature stage and promoting the interdiffusion between elements. (10) The heating rate of the first calcination is 1-15℃ / min, the final temperature is 800-1100℃, and the time is 10-24h; Optionally, the heating rate of the first calcination can be any value between 1℃ / min, 5℃ / min, 10℃ / min, 15℃ / min or 1-15℃ / min, the final temperature can be any value between 800℃, 900℃, 1000℃, 1100℃ or 800-1100℃, and the time can be any value between 10h, 20h, 24h or 10-24h. (11) The heating rate of the second calcination is 1-15℃ / min, the final temperature is 450-800℃, and the time is 4-12h.
[0038] Optionally, the heating rate of the second calcination can be any value between 1℃ / min, 5℃ / min, 10℃ / min, 15℃ / min or 1-15℃ / min, the endpoint temperature can be any value between 450℃, 600℃, 700℃, 800℃ or 450-800℃, and the time can be any value between 4h, 8h, 12h or 4-12h.
[0039] A third aspect of this application provides a positive electrode sheet, comprising the aforementioned sodium-ion battery positive electrode material or a sodium-ion battery positive electrode material prepared by the aforementioned method.
[0040] In some embodiments, the positive electrode typically includes a positive current collector and a positive electrode material layer formed on the surface of the positive current collector. The positive electrode material layer contains a sodium-ion battery positive electrode material as described in any embodiment herein. The positive current collector can be copper foil, aluminum foil, carbon-coated aluminum foil, titanium foil, nickel foil, iron foil, zinc foil, etc., preferably aluminum foil. The positive electrode material layer includes a positive active material, a conductive agent, and a binder. The positive electrode material layer is obtained by coating a positive electrode slurry, including the positive active material, conductive agent, binder, and solvent, onto the positive current collector, followed by rolling, die-cutting, and baking. The solvent can be N-methylpyrrolidone. In an exemplary embodiment, the positive electrode material, conductive agent, binder, and solvent can be mixed and stirred uniformly to obtain a positive electrode slurry. The conductive agent can be one or more commonly used in the art, preferably selected from conductive carbon black (SP), carbon fiber (CF), acetylene black, Ketjen black, graphene, and carbon nanotubes. The adhesive may be one or more commonly used in the art, preferably selected from fluorinated resins, polypropylene resins, fibrous adhesives and polyimide adhesives.
[0041] In some embodiments, the fluorinated resin is polyvinylidene fluoride (PVDF). Based on the total weight of the positive electrode material layer, the mass of the positive electrode active material can be 90wt% to 99wt%, preferably 95wt% to 98wt%, the content of the conductive agent can be 0.5wt% to 5wt%, preferably 1wt% to 3wt%, for example 1wt%, 1.5wt%, 2wt%, 2.5wt%, and the content of the binder can be 2wt% to 4wt%, preferably 1.5wt% to 3wt%, for example 2.5wt%, 3wt%, 3.5wt%.
[0042] A battery typically includes a cell and an electrolyte. The cell comprises a positive electrode, a negative electrode, and a separator. A sodium-ion battery cell is produced by stacking the positive electrode, negative electrode, and separator according to design requirements (e.g., Z-shaped stacking or wound stacking). After obtaining the cell, it is encapsulated in a casing. The process involves drying to remove moisture, injecting electrolyte, encapsulation, settling, formation, and high-temperature aging to obtain the sodium-ion battery. The form of the sodium-ion battery in this invention is not particularly limited; it can be a button-type sodium-ion battery, a cylindrical sodium-ion battery, a pouch sodium-ion battery, or an aluminum-cased sodium-ion battery.
[0043] Therefore, a fourth aspect of this application provides a battery comprising the positive electrode material described in any embodiment herein.
[0044] In an exemplary embodiment, the sodium-ion battery has an initial charge capacity >1330mAh, such as ≥1330mAh or ≥1335mAh, and an initial discharge capacity >1190mAh, such as ≥1220mAh or ≥1250mAh. It is tested at 35°C using a charge-discharge cycle system with a voltage range of 1.5-3.8V and a charge-discharge cycle system of 0.5C / 1C, and at -20°C using a charge-discharge cycle system with a voltage range of 1.5-3.8V and a charge-discharge cycle system of 0.2C / 0.5C.
[0045] The membrane can be a polymer membrane, a ceramic membrane, or a polymer / ceramic composite membrane. Polymer membranes include single-layer polymer membranes and multi-layer polymer membranes. Single-layer polymer membranes include polyethylene (PE) membranes and polypropylene (PP) membranes.
[0046] The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector. The negative electrode current collector can be a material with excellent conductivity commonly used in the art, including but not limited to: copper foil, aluminum foil, carbon-coated aluminum foil, nickel foil, a base coated with conductive polymer, and nickel foam. The negative electrode material layer includes a negative electrode active material, a conductive agent, and a binder. The negative electrode material layer is obtained by coating a negative electrode slurry containing a negative electrode active material, a conductive agent, a binder, and a solvent onto the negative electrode current collector, followed by rolling, die-cutting, and baking. The negative electrode material layer or the negative electrode slurry may also include optional thickeners and / or dispersants. A negative electrode slurry can be prepared by sequentially adding the negative electrode active material, conductive agent, and binder to a solvent, and then further preparing the negative electrode sheet. In an exemplary embodiment, the thickener is dissolved in a solvent, and then a uniformly mixed negative electrode active material, conductive agent, and binder are added. The solvent can be a conventional solvent in the art, such as deionized water. The negative electrode active material can be one or more selected from graphite (including artificial graphite and natural graphite), silicon-carbon negative electrode, metal-based materials (e.g., metal powder, metal fibers, such as copper, nickel, aluminum, silver, etc.), hard carbon, and sodium titanate, preferably hard carbon. The conductive agent is preferably selected from one or more selected from conductive carbon black, carbon fiber, acetylene black, Ketjen black, graphene, and carbon nanotubes. The binder is preferably selected from one or more selected from fluorinated resin, polypropylene resin, fiber-type binder, rubber-type binder, and polyimide-type binder, such as styrene-butadiene rubber (SBR). In some embodiments, the negative electrode active material in the negative electrode material layer is hard carbon, the conductive agent is conductive carbon black, the binder is styrene-butadiene rubber, and the thickener is sodium carboxymethyl cellulose (CMC). The mass ratio of each component in the negative electrode material layer can be conventional. For example, based on the total weight of the negative electrode material layer, the content of the negative electrode active material can be 90wt% to 99wt%, preferably 92wt% to 98wt%, such as 93wt%, 95wt%, 95.7wt%, 96wt%, and 97wt%; the content of the conductive agent can be 0.5wt% to 5wt%, preferably 1.0wt% to 3wt%, such as 1wt%, 1.5wt%, 2wt%, and 2.5wt%; the content of the binder can be 0.5wt% to 5wt%, preferably 1.5wt% to 4wt%, such as 1.8wt%, 2.0wt%, 2.5wt%, 3wt%, and 3.5wt%; and the content of the thickener can be 0.5wt% to 5wt%, such as 1wt%, 1.5wt%, 2wt%, and 2.5wt%.
[0047] Based on a total electrolyte mass of 100%, the electrolyte comprises 70-85% solvent, 10-15% sodium source, and 5-15% additives. The solvent includes one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), 1,2-dimethoxyethane (DME), and triethyl phosphate (TEP). The sodium source includes one of NaDFOB, NaTFSI, NaPF6, NaClO4, NaFSI, and NaBF4. The additives include at least one of FEC, VC, PDO, PTS, DTD, TMSPi, NaFSI, and NaDFOB. In this configuration, the sodium-ion battery exhibits superior cycle performance.
[0048] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0049] Example 1 This embodiment provides a sodium-ion battery cathode material, including a substrate and a coating layer disposed on the surface of the substrate; the substrate has the structural formula: Na 0.95 Ni 0.399 Fe 0.2 Mn 0.399 Ca 0.002 O2, with a coating layer consisting of sodium-containing oxides coated with Ca on the surface, is a single-crystal material.
[0050] The second aspect of this embodiment provides a method for preparing a sodium-ion battery cathode material, the specific steps of which are as follows: S1: Nickel sulfate, ferric sulfate and manganese sulfate were mixed evenly according to the molar ratio Ni:Fe:Mn=0.4:0.2:0.4 to obtain a mixed metal salt solution with a concentration of 2mol / L. Then, a sodium hydroxide solution with a solute mass fraction of 30wt% and an ammonia solution with a solute mass fraction of 23wt% were prepared separately. S2: Add the prepared sodium hydroxide solution, ammonia solution and deionized water to the reactor as the first base solution (pH value 11.7, ammonia concentration 5g / L, temperature 58℃). The mixed metal salt solution, sodium hydroxide solution and ammonia solution are introduced into the reactor in parallel to carry out the first coprecipitation reaction. The stirring speed during the reaction is 850rpm, the nitrogen gas introduction rate is 2L / min, the purity is greater than or equal to 99.5%, and the duration of the first coprecipitation reaction is 44 hours. The pH value, ammonia concentration and temperature are maintained at the same as the first base solution throughout the first coprecipitation reaction to obtain the seed slurry. S3: In the second bottom solution containing seed slurry, sodium hydroxide and ammonia (pH value 10.8, ammonia concentration 5g / L, temperature 58℃), continue to introduce mixed metal salt solution, sodium hydroxide solution and ammonia to carry out the second coprecipitation reaction to obtain hydroxide precursor. During the reaction, control the pH value to gradually decrease from the initial 10.8 to 10.2, and then maintain the pH value until the reactor is stopped. Maintain the stirring speed at 850rpm and the nitrogen gas introduction rate at 2L / min throughout the second coprecipitation reaction. The ammonia concentration and temperature are the same as those of the second bottom solution. S4: Dry the hydroxide precursor and perform SEM testing, as detailed below. Figure 1 As shown, the drying temperature was 110℃ and the time was 5h. The dried hydroxide precursor was mixed with sodium carbonate (the molar ratio of sodium in the hydroxide precursor and sodium source was 1:1.05), and CaCO3 (accounting for 1000ppm of the total mixture) was added for segmented sintering: first, the temperature was increased to 400℃ at a heating rate of 3℃ / min for 8h of pre-sintering in an air atmosphere, and then the temperature was increased to 940℃ at a heating rate of 3℃ / min for 16h of sintering in an air atmosphere. After sintering, the material was cooled in the furnace to obtain Ca-doped calcined material. The material was crushed by a roller mill / airflow crusher and sieved through a 300-mesh sieve for later use. S5: Add CaCO3 (Ca accounts for 5000ppm of the total mixture) to the calcining material, mix evenly, calcine at 750℃ for 7h and cool to room temperature to finally obtain sodium-ion battery cathode material with bulk Ca doping and surface Ca coating.
[0051] The XRD pattern of the sodium-ion battery cathode material is as follows: Figure 2 As shown, the diffraction characteristic peaks of XRD were marked. Based on the XRD diffraction data of Example 1, the diffraction peak intensities of the 003 and 104 crystal planes were calculated using Jade software.
[0052] SEM images of the sodium-ion battery cathode material are shown below. Figure 3 As shown, the primary particle morphology of this sodium-ion cathode material is a hexagonal plate-like particle, and the crystal plane corresponding to the most exposed plane (i.e., the hexagonal upper and lower planes) is the (003) crystal plane, which further indicates that this type of material has good (003) crystal plane preferred orientation and a certain side height.
[0053] Example 2 The difference from Example 1 is that in step S3, the pH value is controlled to gradually decrease from the initial 10.8 to 10.4 during the reaction process, while the other steps are the same.
[0054] Example 3 The difference from Example 1 is that in step S4, after pre-sintering, the temperature is increased to 980°C and sintered for 14 hours at a heating rate of 3°C / min.
[0055] Example 4 The difference from Example 1 is that B2O3 (B accounts for 2000 ppm of the total mixture) was added in step S5.
[0056] Example 5 The difference from Example 1 is that in step S1, nickel sulfate, ferric sulfate, manganese sulfate and copper sulfate are mixed evenly according to the molar ratio Ni:Fe:Mn:Cu=0.3:0.3:0.35:0.05.
[0057] The prepared sodium-ion battery cathode material includes a matrix and a coating layer disposed on the surface of the matrix; the structural formula of the matrix is: Na 0.95 Ni 0.2993 Fe 0.2993 Mn 0.3491 Cu 0.05 Ca 0.0023 O2.
[0058] Example 6 The difference from Example 1 is that in step S4, the dried hydroxide precursor is mixed with sodium carbonate, the molar ratio of the hydroxide precursor to sodium in the sodium source is 1:1.075, and CaCO3 is not added.
[0059] The prepared sodium-ion battery cathode material includes a matrix and a coating layer disposed on the surface of the matrix; the structural formula of the matrix is: Na 0.97 Ni 0.4 Fe 0.2 Mn 0.4 O2.
[0060] Comparative Example 1 The difference from Example 1 is that in step S3, a second coprecipitation reaction is carried out to obtain the hydroxide precursor, and the pH value is controlled to gradually decrease from the initial 11.7 to 11.4 during the reaction.
[0061] SEM images of the prepared precursors are shown below. Figure 4 As shown.
[0062] The XRD pattern of the sodium-ion battery cathode material is as follows: Figure 5 As shown.
[0063] SEM images of the sodium-ion battery cathode material are shown below. Figure 6 As shown.
[0064] Comparative Example 2 The difference from Example 1 is that in step S2, 0.05 mol / L of CTAB (hexadecyltrimethylammonium bromide) surfactant is added.
[0065] The XRD pattern of the sodium-ion battery cathode material is as follows: Figure 7 As shown.
[0066] SEM images of the sodium-ion battery cathode material are shown below. Figure 8 As shown.
[0067] Comparative Example 3 The difference from Example 1 is that CaCO3 is not added in steps S4 and S5.
[0068] The prepared sodium-ion battery cathode material includes a matrix and a coating layer disposed on the surface of the matrix; the structural formula of the matrix is: Na 0.95 Ni 0.4 Fe 0.2 Mn 0.4 O2.
[0069] Comparative Example 4 The difference from Example 1 is that step S5 is not performed, that is, the coating is not performed.
[0070] The sodium-ion battery cathode materials provided in the above embodiments and comparative examples were tested for diffraction peak intensity, average length, average height, D50, and specific surface area of the 003 and 104 crystal planes. The specific test data are shown in Table 1.
[0071] Table 1. Cathode Materials for Sodium-ion Batteries
[0072] Batteries were prepared using the sodium-ion battery cathode materials provided in the above embodiments and comparative examples, and their electrochemical performance was tested. The specific test results are shown in Table 2.
[0073] The specific method for rate testing is as follows: (1) The battery is left to stand for 5 minutes at 25°C; (2) It is charged with a constant current of 0.2C to 3.8V, charged with a constant voltage, and the cut-off current is 0.05C; (3) The battery is left to stand for 5 minutes at 25°C; (4) It is discharged with a constant current of 0.2C to 1.5V; (5) The battery is left to stand for 5 minutes at 25°C; (6) It is charged with a constant current of 0.2C to 3.8V, charged with a constant voltage, and the cut-off current is 0.05C; (7) The battery is left to stand for 5 minutes at 25°C; (8) It is discharged with a constant current of 10C to 1.5V; (9) The 10C / 0.2C discharge capacity retention rate at 25°C is obtained by dividing the 10C discharge capacity by the 0.2C discharge capacity.
[0074] The specific method for the -20℃ cycle test is as follows: (1) The battery is left to stand at -20℃ for 120 minutes; (2) Charge the battery with a constant current of 0.35C to 3.2V, and continue charging with a constant current of 1C to 3.8V, with a cutoff current of 0.05C; (3) Leave the battery to stand at -20℃ for 5 minutes; (4) Discharge the battery with a constant current of 0.5C to 1.5V; (5) Leave the battery to stand at -20℃ for 5 minutes. After repeating steps (2) to (5) 50 times, the capacity retention rate is obtained by dividing the first discharge capacity by the 50th discharge capacity.
[0075] The 35℃ cycle test method is as follows: (1) The battery is left to stand for 5 minutes at 35℃; (2) 1C constant current charging to 3.8V, constant voltage charging, cut-off current 0.05C; (3) 35℃ standing for 5 minutes; (4) 1C constant current discharge to 1.5V; (5) 35℃ standing for 5 minutes; After 1000 cycles of steps (2)-(5), the capacity retention rate is obtained by dividing the first discharge capacity by the discharge capacity of the 1000th cycle, and the cell thickness before and after 1000 cycles is measured with calipers. The thickness expansion rate is obtained according to the formula (thickness after cycle - thickness before cycle) / thickness before cycle.
[0076] Table 2 Electrochemical Performance Tests
[0077] analyze: As can be seen from the above experiments, compared with Example 1, the particle thickness of the material in Example 2 is slightly reduced, but the low-temperature discharge performance does not show significant deterioration, indicating that the cathode material prepared at this pH value has a reasonable structure and good overall electrochemical performance.
[0078] Compared to Example 1, Example 4 introduced element B during the coating process. This did not significantly change the particle size of the material and resulted in better electrochemical performance, indicating that the use of other elements for trace coating did not have a significant impact on the material's performance.
[0079] Compared with Example 1, when the orientation of the 003 peak is higher, that is, the particle exhibits length-direction dominance, it leads to the deintercalation and insertion of Na. + The active surface area is smaller, increasing the amount of Na + The capacity retention rate is lower in the transport path inside the particle at the same discharge rate, especially the capacity retention rate at -20°C, which is significantly worse than that in Example 1.
[0080] Compared to Example 1, the addition of surfactant EDTA in Comparative Example 2 inhibited particle growth perpendicular to the 003 plane, resulting in a preferred growth orientation of the particles in the height direction, effectively reducing Na... + The bulk transport distance was increased, and the Na insertion / extraction was improved. +The increased active surface ratio significantly improves the discharge capacity retention rate at high current and room temperature, while also exhibiting excellent low-temperature cycling capacity retention. However, compared to low-temperature cycling performance, increasing the temperature to 35℃ exacerbates side reactions between the effective active surface 104 crystal plane of the cathode particles (which facilitates sodium ion insertion / extraction) and the electrolyte. These side reactions include: increased cell impedance after interfacial phase transition to an electrochemically inert rock salt phase; and increased catalytic activity of Fe... 4+ This will accelerate the oxidative decomposition of the electrolyte, further leading to a decrease in the cycle capacity retention rate at 35°C.
[0081] Compared to Comparative Example 3, the introduction of doping elements in Example 1 did not significantly affect the length / thickness of the cathode material particles. However, the addition of the dopant Ca significantly improved the capacity retention during high-temperature cycling, indicating enhanced structural stability. Therefore, it is necessary to rationally control the particle length and height of sodium-ion battery cathode materials to balance the capacity retention during low-temperature cycling and high-temperature cycling at 35°C.
[0082] Compared to Example 1, Comparative Example 4 did not involve metal element coating, and the length / thickness of the cathode material particles showed no significant difference. The capacity retention during low-temperature cycling was not significantly affected, indicating that coating does not affect the ion transport performance at the interface. However, the capacity retention during high-temperature cycling decreased significantly, indicating severe interfacial side reactions occurred in the cathode material during high-temperature cycling, leading to deteriorated interfacial kinetics. Therefore, it is necessary to modify the shallow surface layer of the cathode material particles to not only ensure good low-temperature discharge capability but also improve the interfacial structural stability during high-temperature cycling at 35°C.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0084] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A sodium-ion battery cathode material, characterized in that, Includes a substrate and a coating layer disposed on the surface of the substrate; The general structural formula of the matrix is: Na a Ni x Fe y Mn z O2, where 1.05≥a≥0.80, 0.5≥x≥0.1, 0.4≥y≥0.1, 0.8≥z≥0.1; The coating layer comprises an oxide containing M' and sodium; M' includes one or more of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo; Its XRD pattern satisfies the following: the ratio of the diffraction peak intensities of the 003 crystal plane to those of the 104 crystal plane is N, where 1.35≤N≤3.5; The ratio of the average length to the average height of the sodium-ion battery cathode material is M, where 1.02 ≤ M ≤ 10.91; The length of the sodium-ion battery cathode material is 2.0-8.73 μm, and the height is 0.8-1.96 μm; The method for preparing the sodium-ion battery cathode material includes: Nickel salt, iron salt, and manganese salt are first mixed to obtain a mixed metal salt solution; Under a nitrogen atmosphere, a mixed metal salt solution, sodium hydroxide solution and ammonia solution are introduced into a first base solution containing sodium hydroxide and ammonia water to carry out a first coprecipitation reaction to obtain a seed slurry while maintaining a constant pH value. A mixed metal salt solution, sodium hydroxide solution, and ammonia solution are introduced into a second bottom solution containing the seed slurry, sodium hydroxide, and ammonia water to carry out a second coprecipitation reaction to obtain a hydroxide precursor; The hydroxide precursor and sodium source are mixed to obtain a mixture. The mixture is then pre-sintered and first calcined under an oxygen-containing atmosphere to obtain a first calcined material. The first calcined material and the M'-containing compound are mixed in a third time and then calcined in a second time to obtain a sodium-ion battery cathode material. During the first coprecipitation reaction, the pH value is constant; during the second coprecipitation reaction, the pH value gradually decreases.
2. The sodium-ion battery cathode material according to claim 1, characterized in that, At least one of the following conditions must be met: (1) 1.4≤N≤2.35, 1.5≤M≤6.1; (2) The 2θ range of the 003 peak of the sodium-ion battery cathode material is 16.2-16.9, and the 2θ range of the 104 peak is 41.4-41.
8.
3. The sodium-ion battery cathode material according to claim 1, characterized in that, The matrix is also doped with element M, and the general structural formula of the doped matrix is: Na a Ni x Fe y Mn z M 1-x-y-z O2, wherein 1.05≥a≥0.80, 0.5≥x≥0.1, 0.4≥y≥0.1, 0.8≥z≥0.1, 1.0>1-xzy>0; M includes one or more of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
4. The sodium-ion battery cathode material according to any one of claims 1-3, characterized in that, At least one of the following conditions must be met: (1) The D50 of the sodium-ion battery cathode material is 1.0-12 μm; (2) The specific surface area of the sodium-ion battery cathode material is 0.2-1.5 m². 2 / g.
5. The sodium-ion battery cathode material according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The nickel salt includes nickel sulfate; (2) The iron salts include ferric sulfate; (3) The manganese salt includes manganese sulfate; (4) The M'-containing compound includes one or more of the oxides, chlorides, fluorides, hydroxides, carbonates, nitrates and acetates of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La and Mo; (5) The sodium source includes one or more of sodium carbonate, sodium hydroxide, and sodium acetate; (6) When performing the first mixing and / or the second mixing, a compound containing M is also added, said compound containing M including one or more oxides, chlorides, fluorides, hydroxides, carbonates, nitrates and acetates of Li, Al, Mg, Co, Zr, W, B, Sr, Ba, Sn, Ca, Nb, Cu, Zn, Ti, Y, La, and Mo.
6. The sodium-ion battery cathode material according to claim 5, characterized in that, At least one of the following conditions must be met: (1) During the first mixing, the molar ratio of nickel in the nickel salt, iron in the iron salt, and manganese in the manganese salt is 0.1-0.5: 0.1-0.4: 0.1-0.8; (2) The molar ratio of the hydroxide precursor to sodium in the sodium source is 1:0.85-1.15; (3) The mass of M' in the M'-containing compound accounts for 500-8000 ppm of the mass of the mixture obtained by the third mixing; (4) The mass of M in the M-containing compound accounts for 500-10000 ppm of the mass of the mixture obtained by the second mixing.
7. The sodium-ion battery cathode material according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The pH value of the first base solution and the first coprecipitation reaction is 11.2-11.9; (2) The time for the first coprecipitation reaction is 40-48 hours; (3) The alkalinity of the first coprecipitation reaction and the second coprecipitation reaction are each 3-9 g / L, and the temperature is each 55-65℃. (4) The pH value of the second substrate is 10.5-11.0; (5) The endpoint pH value of the second coprecipitation is 10-10.4; (6) The second coprecipitation time is 36-48 hours; (7) The purity of nitrogen in the nitrogen atmosphere is greater than or equal to 99.5%; (8) Before the second mixing, the hydroxide precursor is dried at a temperature of 100-300°C for 2-6 hours. (9) The heating rate of the pre-sintering is 1-15℃ / min, the final temperature is 400-550℃, and the time is 4-12h; (10) The heating rate of the first calcination is 1-15℃ / min, the final temperature is 800-1100℃, and the time is 10-24h; (11) The heating rate of the second calcination is 1-15℃ / min, the final temperature is 450-800℃, and the time is 4-12h.
8. A positive electrode sheet, characterized in that, Includes the sodium-ion battery cathode material according to any one of claims 1-7.
9. A battery, characterized in that, Includes the positive electrode sheet as described in claim 8.
Citation Information
Patent Citations
Two-phase composite sodium ion battery positive electrode material and preparation method and application thereof
CN116979032A
Sodium-ion battery positive electrode material and preparation method thereof, sodium-ion battery and power-related equipment
CN119601630A
Sodium battery positive electrode material and preparation method, precursor and application thereof
CN120600741A